Representação distrital e coalizões legislativas : o impacto da sobrerrepresentação nas votações no Congresso brasileiro - Kauchakje, Samira (2017)
This thesis addresses the relationship between mallaportionment and legislative behavior, precisely, the effects of overrepresentation on legislative outcomes, It is well established that overrepresented subnational units benefit disproportionately from resources distributed by the central government. Explanations for this fact are based on a model of legislative bargaining over distributive projects. Therefore, the focus of this investigation is the legislative coalitions. However, this model assumes legislators who are elected in single-member districts, where there is a one-to-one correspondence between the legislator and the district. In these systems, defining the interest of the district is straightforward and the legislator can easily claim credit for defending it. The same is not true in multi-member districts where interests that successfully seek representation are varied and legislators elected from the same district can claim to represent different constituencies. So, the goal of this research is to prove the applicability of the legislative bargaining mechanism in a multi-member district electoral system. The central assumption is that in multi member electoral districts, legislative coalitions cut-across the apportionment cleavage and wash out the impact that overrepresentation might have had under a single-member electoral structure. I test this claim by comparing legislative coalitions in the Brazilian Chamber of Deputies and the Senate between 1989 and 2014 and examined the pattern of transferences of federal funds of the central government to subnational units of the country. While both Brazilian houses are symmetric in their power, elections for the former are based on proportional representation electoral systems in large districts and for the later on majority rules in one or two-member districts. I performed three types of descriptive statistical analyses: voting unit analysis; dyadic analysis and winning coalitions analysis. The results showed that the relation between the higher volume of fiscal transferences and overrepresentation is stronger in the Senate. In turn, it was demonstrated that, although the effects of overrepresentation on the coalitions is also higher in the Senate; in general, the impact of malapportionment in the congress is discreet. Thus, denying the expectations disseminated by the literature, the legislative bargain for distributive projects is not, necessarily, the underlying mechanism to distortion in the discretionary distribution of social resources which favors the overrepresented units.